Joining Voices: University – Industry Partnerships in the Humanities - Siemens, Lynne (KULA, 2019)
University-industry partnerships are common in the Sciences, but less so in the Humanities. As a result, there is little understanding of how they work in the Humanities. Using the Implementing New Knowledge Environments: Networked Open Social Scholarship (INKE:NOSS) initiative as a case study, this paper contributes to this discussion by examining the nature of the university-industry partnership with libraries and academic-adjacent organizations, and associated benefits, challenges, measures of success, and outcomes. Interviews were conducted with the collaboration’s industry partners. After several years of collaboration on the development of a grant application, industry partners have found the experience of working with academics to be a positive one overall. Industry partners are contributing primarily in-kind resources in the form of staff time, travel to meetings, and reading and commenting on documents. They have also been able to realize benefits while negotiating the challenges. Using qualitative standards, measures of success and desired outcomes are being articulated. This work developing the partnership should stand the larger INKE:NOSS team in good stead if they are successful with securing grant funding.